2021
DOI: 10.3390/geriatrics6030091
|View full text |Cite
|
Sign up to set email alerts
|

The Mini-Cog, Clock Drawing Test, and Three-Item Recall Test: Rapid Cognitive Screening Tools with Comparable Performance in Detecting Mild NCD in Older Patients

Abstract: Background: Early mild neurocognitive disorder (mild NCD) detection can allow for appropriate planning and delay disease progression. There have been few studies examining validated mild NCD detection tools. One such tool that may be of use is the Mini-Cog, which consists of the clock drawing test (CDT) and three-item recall. Methods: This study aimed to compare the diagnostic properties of the Mini-Cog, the CDT alone, and the three-item recall test alone in mild NCD detection according to DSM-5 criteria. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This study provided evidence to support the use of simple neuropsychological testing to differentiate cognitive performance among older adults without and with MCI. These tests are reliable, valid and easy to administer in the community setting ( Baiyewu et al, 2005 ; Schmidtke and Olbrich, 2007 ; Limpawattana and Manjavong, 2021 ). Furthermore, our results demonstrated an early decline in cognitive inhibition; thus, we suggest that screening and prevention should begin in early adults to prevent or slow the decline in cognitive inhibition in older adults and its progression to MCI.…”
Section: Discussionmentioning
confidence: 99%
“…This study provided evidence to support the use of simple neuropsychological testing to differentiate cognitive performance among older adults without and with MCI. These tests are reliable, valid and easy to administer in the community setting ( Baiyewu et al, 2005 ; Schmidtke and Olbrich, 2007 ; Limpawattana and Manjavong, 2021 ). Furthermore, our results demonstrated an early decline in cognitive inhibition; thus, we suggest that screening and prevention should begin in early adults to prevent or slow the decline in cognitive inhibition in older adults and its progression to MCI.…”
Section: Discussionmentioning
confidence: 99%
“…The participants of this study were recruited from data from the “The performance of the Rowland Universal Dementia Assessment Scale (RUDAS), Recall test, and Mini-Cog in the screening of mild cognitive impairment” project [ 28 , 29 ], which was conducted during January 2020 and March 2021 at an outpatient setting of the department of Internal Medicine of the Srinagarind University Hospital, Khon Kaen University, Thailand. Subjects were older patients aged ≥60 years by Thai definition without evident acute illness that could influence the performance of the Thai version of RUDAS (RUDAS-Thai) and the MoCA (MoCA-Thai), for example, delirium, infection, acute cerebrovascular disease, and acute heart attack.…”
Section: Methodsmentioning
confidence: 99%
“…It, however, is a good tool to detect cognitive impairment. In addition, the recent study regarding the Mini-Cog test in Thai showed that it had acceptable performance and was not affected by education [35]. Therefore, this study used "cognitive impairment" rather than "dementia."…”
Section: Discussionmentioning
confidence: 99%